Reducing carbon emission in the goat farms by switching from conventional goat farming to green goat farm typology - Canan, Selime (Frontiers in Environmental Science, 2023)
There have been studies that measure the greenhouse gas emissions of farms without considering typological differences. However, in these studies, goat farms were not divided into groups in terms of their characteristics, their typologies were not determined and green gas emissions was not revealed in terms of farm typology. This situation had a negative impact on the environmental protection of goat farms and caused wastage of government resources allocated to the environmental protection. This deficiency has been tried to be eliminated to a great extent over time, and researchers have turned to analyzes of greenhouse gas emission measurement of goat products instead of determining the typologies of farms. The study sought answers to the questions of what the typologies of goat farms in Turkey are, whether greenhouse gas emissions change in terms of typologies, and whether a typologically differentiated approach can be adopted to support goat farms for environmental protection. So, my manuscript's relevance to the journal and specialty section that " Nexus between innovations, environmental challenges and labor mobility".